Slavistična prepletanja 6 (University of Maribor Press, 2025)
Slavic Intertwining 6. The monograph contains nine contributions focused on research into Slavic languages and literature. The first section highlights the literary creativity of younger Slovenian female writers and explores the characteristics and issues of South Slavic inter-literary reception in contemporary times. It also analyses the well-known poem “Juri Muri po Sloveniji” (Juri Muri around Slovenia), which can be interpreted as a guide to cultural heritage. The second section begins with three contributions on phraseology that examine animals in comparative idioms in Slovenian, Croatian, Macedonian, and Russian; the themes of wealth and poverty in Slovenian and Ukrainian; and the phraseological equivalents between Slovenian and Croatian. Next, there is a study of selected aspects of presidential speeches and inaugural addresses, an analysis of morphological errors made by Macedonian speakers when learning Slovenian, and a presentation on using excursions as a teaching method for acquiring Slovenian, particularly as a second or foreign language.